2018
DOI: 10.1177/0018726718793930
|View full text |Cite
|
Sign up to set email alerts
|

Turning vice into virtue: Institutional work and professional misconduct

Abstract: Why do professionals engage in or aid misconduct, rather than rejecting it as a threat to their legitimacy and labor market survival? This article contributes to the scholarly agenda by drawing on an ethnographic study of professionals who facilitate offshore tax avoidance for the ultra-wealthy. This form of expert advisory work has become highly controversial, and is increasingly classified as a form of professional wrongdoing. Building on theories of institutional work and categorization, the study theorizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Lander et al (2018) -differences according to careers stage create heterogeneous understandings Radaelli et al (2018) -the specificities of misconduct in any particular setting (in their case medical education) complicate singular definitions The antecedents of professional misconduct What factors render social and symbolic boundaries more or less important, interdependent and effective or ineffective in professional misconduct? Harrington (2018) and Roulet (2018) -the boundaries between clients and professionals are dissolved in ways that encourage misconduct Are there new symbolic boundaries that need to be taken account of and why? Lander et al (2018) -the symbolic boundary between junior and senior professionals affects the likelihood of misconduct Who do professionals interact with, and how do these interactions influence the nature, antecedents and consequences of professional misconduct?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lander et al (2018) -differences according to careers stage create heterogeneous understandings Radaelli et al (2018) -the specificities of misconduct in any particular setting (in their case medical education) complicate singular definitions The antecedents of professional misconduct What factors render social and symbolic boundaries more or less important, interdependent and effective or ineffective in professional misconduct? Harrington (2018) and Roulet (2018) -the boundaries between clients and professionals are dissolved in ways that encourage misconduct Are there new symbolic boundaries that need to be taken account of and why? Lander et al (2018) -the symbolic boundary between junior and senior professionals affects the likelihood of misconduct Who do professionals interact with, and how do these interactions influence the nature, antecedents and consequences of professional misconduct?…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported in this special issue illustrate the complex nature of professional misconduct. Harrington (2018) shows how misconduct manifests at the institutional level when 'practitioners acquire the moral justification necessary to perpetuate misconduct' (Harrington: 24). Professionals re-categorize tax avoidance so that it does not now constitute professional misconduct but a sensible and entirely rational corporate practice.…”
Section: The Nature Of Professional Misconductmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, models feature IW as one part of a larger model. For example, in her model of professional misconduct, Harrington (2019) situates IW between triggering events (contestation) and possible outcomes (self-authorization). The model places IW as one step in a process.…”
Section: Theme 5: Representations -Seeds Of An Ideamentioning
confidence: 99%
“…Methodologically, these practical implications and shifts in conceptual focus foreground the need for two distinctive data collection and analysis strategies. First, ethnographic immersion (Harrington 2015b(Harrington , 2017c)-a technique based on anthropological fieldwork-has proven particularly enlightening in the study of social and cultural capital as facilitators of mobility for transnational professionals. Indeed, the sociology of the professions would benefit from greater attention to work by anthropologists on transnational professionals: Research in this stream has steadily built theory on key issues relevant across the social sciences, such as the micro-macro link in globalization.…”
Section: Implications and An Agenda For Future Researchmentioning
confidence: 99%